PERAN PR DALAM MENGHADAPI BISNIS PROSTITUSI ONLINE: STUDI KASUS KAMPANYE KOMNAS PEREMPUAN DI PLATFORM DIGITAL - Muhammad Zein Septiana; Lukman (An Nafi': Multidisciplinary Science, 2025)
Using a descriptive qualitative approach, the research focuses on PR digital campaign strategies through in-depth interviews, document studies, and observation of online campaign activities. The findings show that KOMNAS Perempuan’s PR employs preventive and educational communication through social media, websites, and influencer collaborations to raise public awareness about digital sexual exploitation. However, challenges such as misinformation, algorithmic bias, and diverse audience interpretation affect message effectiveness. The study concludes that strategic PR communication is essential to building informed public perspectives and promoting gender-sensitive digital advocacy.